26. APPLICATION OF PATIENT-SPECIFIC ORIENTATION FRAME INTO OSTEOTOMY OF DISTAL RADIUS MALUNION AT MILITARY HOSPITAL 175 (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the initial results of osteotomy of distal radius malunion with the application of patient-specific orientation frame at Military Hospital 175.Subject and method: 3 patients with distal radius malunion who underwent osteotomy with the application of patient-specific orientation frame at Military Hospital 175 had data collected from May 2023 to July 2024 according to the prospective research method, describing a series of cases.Results: Through a survey of 3 patients with right distal radius malunion, with the time from the first injury to hospitalization ranging from 2 to 7 months, two cases with the application of patient-specific orientation frame during surgery, the surgery time began to be shortened gradually, reducing the number of direct X-rays during surgery compared to the case without the application of patient-specific orientation frame. The cases had improvements in the indexes of ulnar variance, ulnar tilt angle, and volar angle.Conclusion: This report initially shows the results of anatomical restoration of the distal radius, demonstrating that 3D printing technology creates some advantages when applied in osteotomy of distal radius malunion.
Keywords: Osteotomy; Distal radius malunion; Patient-specific orientation frame